2014
DOI: 10.1016/j.ajpath.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

MFG-E8 Regulates Angiogenesis in Cutaneous Wound Healing

Abstract: Our research group recently demonstrated that pericytes are major sources of the secreted glycoprotein and integrin ligand lactadherin (MFG-E8) in B16 melanoma tumors, and that MFG-E8 promotes angiogenesis via enhanced PDGF-PDGFRβ signaling mediated by integrin-growth factor receptor crosstalk. However, sources of MFG-E8 and its possible roles in skin physiology are not well characterized. The objective of this study was to characterize the involvement of MFG-E8 in skin wound healing. In the dermis of normal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 36 publications
2
70
0
Order By: Relevance
“…We recently demonstrated that MFG-E8 regulates angiogenesis and wound healing in a cutaneous wound healing mice model (Uchiyama et al, 2014). In the present study using a murine I/R model, we additionally determined that MFG-E8 regulates the functions of M1 macrophages, including the secretion of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We recently demonstrated that MFG-E8 regulates angiogenesis and wound healing in a cutaneous wound healing mice model (Uchiyama et al, 2014). In the present study using a murine I/R model, we additionally determined that MFG-E8 regulates the functions of M1 macrophages, including the secretion of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 96%
“…We previously determined that pericytes were the major sources of MFG-E8 in B16 melanoma tumors, and that MFG-E8 localized in close proximity to pericytes/vascular SMCs in the dermis of murine and human skin (Motegi et al, 2011a;Uchiyama et al, 2014). In addition, immunofluorescence staining of skin in the I/R site showed that the MFG-E8 expression levels around blood vessels were enhanced during ischemia.…”
Section: Expression Of Mfg-e8 In Pericyte-like Cells Endothelial Celmentioning
confidence: 97%
See 1 more Smart Citation
“…The carboxy-terminal domains of MFG-E8 can bind to negatively charged phospholipids (20), resulting in the opsonization of apoptotic cells for uptake by phagocytes (19, 21). In addition, interactions between MFG-E8 and integrin αv have been implicated in the enhancement of angiogenesis in mice (22-24). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence has suggested that MFG-E8 protects against acute inflammatory injury in numerous organs such as lung, brain, and intestines [Ajakaiye et al, 2012; Aziz et al, 2012; Cheyuo et al, 2012]. Recently, MFG-E8 has been found to regulate osteoclast homeostasis and inflammatory bone loss as well as angiogenesis in cutaneous wound healing [Abe et al, 2014; Uchiyama et al, 2014]. It inhibits inflammasome-induced IL-1β production and limits postischemic cerebral injury [Deroide et al, 2013].…”
Section: Introductionmentioning
confidence: 99%